The Capacity of Posyandu Cadres Through Complementary Food for Children by Training - Trini Sudiarti; Tiara Amelia; Indah Jamiatun Hasanah (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
Nutritionist from Center of Public Health Beji stated that there are still many cadres who have not participated in training on complementary foods for children under two years (baduta). Likewise, nutritional counseling is rarely done in Integrated Services Post (Posyandu) because of the limited knowledge and resources of adequate cadres. The results of research findings in the Depok city area showed that the mothers have knowledge about nutrition and complementary children’s foods is still lacking. The community service program was carried out in the form of training involving 10 Posyandu represented by 28 cadres from Beji and East Beji Villages. The cadres’ engagement method is in a form of training. The purpose of training is to improve the nutrition, knowledge of complementary foods for children, and the skills of cadres in information & education, and counseling. The training took place on 29-30 August 2019. The facilitator from the Depok City Health Office, Center of Public Health Beji, and Universitas Indonesia. Cadres practiced information & education in Posyandu with the target of 129 infant mothers and counseling for twenty mothers under two years of children. The success of training is measured through pre-test and post-test for cadres and observations of skill cadres. An increase in cadre knowledge score after training by 11 points and category knowledge of cadres are sufficient and good. The results of cadre observations while information & education showed there were still shortcomings in terms of verbal reinforcement skills and fun activities such as singing. Cadre counseling activities still need to be improved in terms of conducting studies such as looking at maternal as child health books also recording counseling results. Training of cadres can improve the knowledge of complementary foods and skills of communication & education also counseling for the mother’s baduta